Glutathione S‐transferase genes and the risk of type 2 diabetes mellitus: Role of sexual dimorphism, gene–gene and gene–smoking interactions in disease susceptibility: 谷胱甘肽S‐转移酶基因与2型糖尿病风险:两性异形、基因‐基因以及基因‐吸烟相互作用对疾病易感性的影响. Issue 5 (2nd January 2018) - Azarova, Iuliia; Bushueva, Olga; Konoplya, Alexander; Polonikov, Alexey
Abstract: Background: Compromised defense against reactive oxygen species (ROS) is considered important in the pathogenesis of type 2 diabetes mellitus (T2DM); therefore, genes encoding antioxidant defense enzymes may contribute to disease susceptibility. This study investigated whether polymorphisms in genes encoding glutathione S‐transferase M1 ( GSTM1 ), T1 ( GSTT1 ), and P1 ( GSTP1 ) jointly contribute to the risk of T2DM. Methods: In all, 1120 unrelated Russian subjects (600 T2DM patients, 520 age‐ and sex‐matched healthy subjects), were recruited to the study. Genotyping was performed by multiplex polymerase chain reaction (PCR; del/del polymorphisms of GSTM1 and GSTT1 ) and TaqMan‐based PCR (polymorphisms I105V and A114V of GSTP1 ). Plasma ROS and glutathione levels in study subjects were analyzed by fluorometric and colorimetric assays, respectively. Results: Genotype del/del GSTT1 was significantly associated with the risk of T2DM (odds ratio [OR] 1.60, 95% confidence interval [CI] 1.17–2.21, P  = 0.003). Gender‐stratified analysis showed that the deletion genotypes of GSTM1 (OR 1.99, 95% CI 1.30–3.05; P  = 0.0002, Q  = 0.016) and GSTT1 (OR 2.23, 95% CI 1.22–4.09; P  = 0.008, Q  = 0.0216), as well as genotype 114A/V of GSTP1 (OR 2.85, 95% CI 1.44–5.62; P  = 0.005, Q  = 0.02) were associated with an increased risk of T2DM exclusively in males. Three genotype combinations (i.e. GSTM1 + ×  GSTT1 +, GSTM1 + ×  GSTP1 114A/A and GSTT1 + ×  GSTP1 114A/A) showed significant associations with a decreased risk of T2DM in males. Conclusions: This study demonstrates, for the first time, that genes encoding glutathione S‐transferases jointly contribute to the risk of T2DM, and that their effects on disease susceptibility are gender specific. Abstract : Highlights This study demonstrates that genes encoding glutathione S‐transferases M1, T1, and P1 are important determinants of susceptibility to type 2 diabetes mellitus (T2DM) in Russians. This study is the first to show a joint contribution of these genes to the development of the disease, but the effects of these genes on disease risk are gender specific. A synergy between the effects of glutathione S‐transferase gene polymorphisms and cigarette smoking may increase the risk of T2DM.